Content validation and apparent check list adapted for surgical material count - Cavalcante, Antonia Abigail do Nascimento (2022)
Validate an adapted checklist for counting surgical material. This is a methodological study developed using face and content validation, and the integrative review was used as a search method that supported the adaptation of the proposed checklist and strengthened the relevance of the research for the safety of surgical patients. For this purpose, seven expert judges participated in the validation of the checklist instrument. And the Content Validity Index (CVI) was adopted as an agreement rate equal to or greater than 0.80. The results show that the instrument under analysis obtained a score of 0.95 in its overall assessment in relation to content validation, and the CVI found was 0.97 in relation to apparent validation, which reveals the approval of the instrument in relation to the content and appearance. Thus, the need for instruments and actions that promote the safety of patients and professionals related to the surgical environment is perceived, as patient safety is an essential dimension of the quality of health care. The correct use and understanding by professionals of this instruments important to solidify the centrality of patient care, providing more effective communication between professionals in the multidisciplinary teams, thus ensuring the practice of safe surgery.